The Urgency of Forming Regional Regulations Concerning Regional Cooperation in Wonosobo District - Suryana, Eka Pala; Rizal, Muhammad; Palestina, Firdaus Ayu (Socio Legal and Islamic Law, 2024)
The dynamics of development in Wonosobo Regency in the last decade have given rise to several collaboration initiatives between parties as mandated in article 363 of Law number 23 of 2014 concerning Regional Government. Relevant to this, a Regional Regulation is needed which will become the umbrella or legal basis for efforts to explore opportunities for regional cooperation efforts in Wonosobo Regency. This research is about the urgency of forming Regional Regulations, especially Wonosobo Regency and also about the concept of effective and efficient cooperation. This research uses normative legal research methods with a focus on applicable laws and regulations, especially those related to regulations regarding regional cooperation. The urgency of forming regional regulations regarding regional cooperation in Wonosobo Regency is as a legal umbrella that explains in detail the concept of regional cooperation. Concepts or models of cooperation that can be applied are knowledge cooperation, standardization cooperation, implementation cooperation, functional cooperation, structural cooperation and philanthropic cooperation. Therefore, it is recommended that the Wonosobo Regency government form a Regional Regulation regarding regional cooperation and the concept or model of this cooperation